Nature connection and its relationship with mindfulness and well-being : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, Massey University, Albany, New Zealand - Capizzi, Robert (Massey University, 2022)
Humans evolved in nature as a creation of nature, ultimately resulting in a profound connection that has shaped the foundations of our nervous system. Throughout history humans have gone to considerable lengths to maintain contact with nature based on the notion that natural environments promote physical and psychological well being. Recent literature has begun to explore the relationship between nature connection, well being and mindfulness in detail. Much of the previous literature focused on exploring the effects of nature through subjecting people to a nature based therapeutic intervention, whereas this research investigated the benefits of nature connection on well being and mindfulness within the general population in the context of their daily lives. This investigation explored the relationship within a general population sample in Auckland, New Zealand. Participants (n = 472) completed a survey questionnaire measuring nature connectedness, hedonic well being, eudemonic well being, stress, mindfulness and average time spent in nature per month. The results yielded a significant positive relationship between nature connection and positive affect, overall meaning in life, presence of meaning, overall mindfulness and the observing, describing, non reactivity and non judgemental facets of mindfulness. Additionally, nature connection was significantly associated with less perceived stress, and time spent in nature was significantly associated with nature connectedness. These findings support the previous literature that suggest a cyclical relationship where nature exposure leads to positive well being outcomes and increased nature connection, therefore increasing the probability of re-engaging with nature. Furthermore, natural settings appear to facilitate mindfulness and mindful techniques can be utilised to develop connectedness and experience positive well being outcomes more efficiently. While these findings have been observed previously in the context of an intervention, this study demonstrates these effects in the general population in terms of their everyday lives, indicating that along with short term benefits, there are also long term benefits on well being from nature connection.
Keywords: 520304 Health psychology